Comparative Study of Vietnam's RCEP and CPTPP Membership: Political-Economic Impacts in ASEAN - Sari, Dewi Fortuna; Prayogo, Neola Hestu (Kemudi, 2025)
This study analyzes the impactsof Vietnam's participation in two multilateral free trade agreements within the Asia-Pacific: the Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP) and the Regional Comprehensive Economic Partnership (RCEP).Using Ivan Gonzalez-Pujol's (2024) hedgingstrategytheory approach, this study aims to examine how these different agreements impact Vietnam's economy, political standing, and regional integration. The study employs a descriptive qualitative method, utilizing secondary dataderived from Vietnam's economic data and recent research on the implementation of RCEP and CPTPP in Vietnam. The results show that Vietnam's membership in RCEP and CPTPP both enhance Vietnam's economic growth and political standing, even throughdifferent pathways. Vietnam's membership in RCEP positions it as a regional manufacturing hub and enhances its export potential among member nations, which include significant economies like China, Japan, and South Korea.However, RCEP presents challenges in the form of increased competition, requiring Vietnam to improve standards and competitiveness. Meanwhile, participation in CPTPP has driven institutional reforms and domestic policy regulations to enhance transparency, resulting in a significant increase in trade volume. Politically, Vietnam's participation in these two agreements strengthens its geopolitical bargaining position in the Asia-Pacific region. To enhance regional integration while maintaining balanced relations with major powers, Vietnam utilizes economic diplomacy, such as the CPTPP and RCEP. This move aligns with the Vietnamese leadership's view that expanding regional cooperation can enhance the regime's legitimacy domestically and benefit the economy.